Diseminasi Hukum Child Rights Protection Sebagai Mitigasi Risiko Perkawinan Pada Usia Anak Dalam Bingkai Otonomi Desa - Budiyono; Yusdiyanto; Ridlwan, Zulkarnain; Saleh, Ahmad; Firmansyah, Ade Arif; Evendia, Malicia (Jurnal Mitrawarga, 2024)
Children have an important role in determining the quality of a nation's civilization. It is no wonder that preparing the next generation of the nation is an important dimension for state administrators. The guarantee for the protection of children's rights is not only regulated in the Indonesian constitution, but also emphasized in UU No.23 Tahun 2002 jo. UU No.17 Tahun 2016 on Child Protection. Various parties are obliged and responsible for ensuring the fulfillment of children's rights, starting from the smallest institutions, namely the family, community, village/kelurahan government, sub-district, district / city government, provincial government and government. Child rights protection is one of the important foundations that must be understood by all parties, including the village government as the government unit closest to the community. This is also part of realizing sustainable development through the fulfillment of children's rights. A rampant case and a problem for the Indonesian nation is the high rate of marriage at the age of a child. This community service activity aims to educate the community, especially the village government, about child rights protection as an effort to mitigate the risk of marriage at a child's age. This is important because the protection of children's human rights has been regulated in various laws and regulations in Indonesia, including the government's efforts to prevent child marriage. This is important for the community to understand so that they can avoid child marriage as a legally protected child right. This activity is a preventive solution to reduce the number of marriages at the age of children. So that the target audience in this activity is the community from various elements, BPD, and the Village Government. The location of the activity was Fajar Baru Village, South Lampung Regency. The methods used in this activity are through lectures, and discussions.